Pengaruh Lingkungan Pertemanan terhadap Gaya Hidup Mahasiswa - Ubaidillah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2024)
The friendship environment is a social factor that has a significant influence on shaping students' lifestyles. In campus life, students tend to engage in intense social interactions with peers, which influence their behavior patterns, clothing styles, time usage, and even daily consumption habits. Technological developments and social trends also make it easier for students to follow the lifestyles developing within their friendship environment. Therefore, this study was conducted to determine the influence of the friendship environment on students' lifestyles. This study used field research with a quantitative approach. Data collection techniques were carried out through interviews, observation, and documentation. Interviews were conducted with students to obtain information about the influence of the friendship environment on daily life. Observations were conducted by observing student behavior within the campus social environment, while documentation was used as supporting data for the study. The data obtained were then analyzed descriptively to determine the relationship between the friendship environment and students' lifestyles. The results showed that the friendship environment has a significant influence on students' lifestyles. Students tend to follow the habits of their friendship groups in various aspects of life, such as social patterns, social media use, clothing styles, and consumer behavior. A positive friendship environment can shape a disciplined and productive lifestyle, while a less positive friendship environment can cause students to prioritize entertainment over academic activities.